2021
DOI: 10.3390/vaccines9040324
|View full text |Cite
|
Sign up to set email alerts
|

BNT162b2 Vaccine Encoding the SARS-CoV-2 P2 S Protects Transgenic hACE2 Mice against COVID-19

Abstract: BNT162b2 is a highly efficacious mRNA vaccine approved to prevent COVID-19. This brief report describes the immunogenicity and anti-viral protective effect of BNT162b2 in hACE2 transgenic mice. Prime-boost immunization with BNT162b2 elicited high titers in neutralizing antibodies against SARS-CoV-2, which correlated with viral clearance and alleviated lung lesions in these mice after viral challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Spikes from VOCs are being investigated as second-generation vaccine candidates to tackle the challenges associated with protection against SARS-CoV-2 emerging variants [34][35][36][37] and therefore, studying the immune response to Spike variants in natural infection can provide insight into differential Spike immunogenicity. We show that infection with B.1.1.7 elicits a robust neutralizing antibody response against B.1.1.7, P.1 and WT variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spikes from VOCs are being investigated as second-generation vaccine candidates to tackle the challenges associated with protection against SARS-CoV-2 emerging variants [34][35][36][37] and therefore, studying the immune response to Spike variants in natural infection can provide insight into differential Spike immunogenicity. We show that infection with B.1.1.7 elicits a robust neutralizing antibody response against B.1.1.7, P.1 and WT variants.…”
Section: Discussionmentioning
confidence: 99%
“…To counter such mutations and their attendant antigenic changes, vaccines using the Spike proteins from these variants of concern (VOCs) are under investigation. [34][35][36][37] Whether the variant Spikes will elicit a robust neutralizing response with superior cross-neutralizing activity against parental strains and newly emerging variants has not been extensively studied. 26,38,39 Natural infection provides an important opportunity to compare the neutralizing antibody titres and cross-neutralizing activity generated from individuals exposed to different Spike variants and will give insights into how mutations in Spike impact immunogenicity, thereby informing the design of second generation vaccine candidates based on VOCs.…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that immune response kinetics after mRNA vaccination are more rapid than with three other leading vaccine technologies. Multiple studies have demonstrated that mRNA vaccines elicit strong antibody responses in various mouse models [18][19][20][21], as well as robust germinal center responses [22] that may be associated with neutralizing antibody generation [23]. Although a wealth of information has been gained regarding antibody responses induced by mRNA vaccines at later timepoints, the early and immediate humoral immune kinetics of mRNA vaccines remains unclear.…”
Section: Humoral Immune Kinetics In Mice Immunized With Hiv-1 Env Mrna Vaccinementioning
confidence: 99%
“… 41 BNT162b2 is a modRNA vaccine that expresses P2 mutant, prefusion spike glycoprotein (P2 S) (version 9). 42 , 43 …”
Section: Delivery Of Mrna Vaccinesmentioning
confidence: 99%